Profile diversity of galacto-oligosaccharides from disaccharides to hexasaccharides by porous graphitic carbon liquid chromatography-orbitrap tandem mass spectrometry. (1st October 2022) - Lin, Chih-Chieh; Yang, Yen-Chiao; Lu, Zhen-Yu; Bagal-Kestwal, Dipali R.; Lu, Ting-Jang
Graphical abstract: Highlights: An improved PGC-LC-Orbitap MS/MS method revealed the diversity of GOS with DP2-DP6. The system separated and identified 58 linear and 10 branched GOS. Fifteen major group components with DP2-DP5 comprised over 65% of total GOS content. Non-reducing GOS components with DP2-DP6 comprised 2.8–7.6% of total GOS content. The major structural diversity occurred in DP3-DP5 GOS. Abstract: Galacto-oligosaccharides (GOS) are important prebiotic supplements for commercial nutraceutical food. The prebiotic efficacy of functional GOS is dependent on their chemical profile. Screening potential markers aids specifications and quality control of GOS materials. However, profiling analysis of GOS with a degree of polymerization (DP) ≥ 4 is still challenging. This study presents a porous graphitic carbon liquid chromatography-orbitrap tandem mass spectrometry-based method that characterized 58 linear and 10 branched GOS and detected 59 non-reducing GOS from DP2 to DP6. The results indicated that 15 major group components with DP2-DP5 accounted for more than 65% of total GOS content in GOS samples, while non-reducing GOS components accounted for only 2.8–7.6%. Substantial variations in components occurred in samples from different batches and sources. Structural and constitutive diversity were dominated by DP3-DP5. This method can help control the quality of GOS products and be used to investigate the structural and prebiotic-efficacy relationships.